ADVANTAGES AND DISADVANTAGES OF THE ONLINE EDUCATION SYSTEM IN OUR SOCIETY (Academia Science Repository, 2023)
In today's rapidly developing country, the High opportunities and facilities given to education are not ignored by everyone. Also included is the rapid penetration of the distance learning system, which is considered a new direction in education. This article reflects on the importance, advantages and disadvantages of the online education system.